Two Stroke Double Power Ecological Engine with Spark Assisted Compression Ignition - Iwan Harianton; Iman Kartolaksono Reksowardojo; Noval Lilansa; Ayi Ruswandi; Beny Bandanajaya; Suwadi Suparlan (Technological Innovation in Engineering Research Vol. 7, 2022)
Due to several unresolved issues such as higher pollutant, fuel consumption, and impractical oiling in the combustion chamber, the automotive industry has almost completely excluded two stroke engines from urban development. Even so, it still encourages an unforgettable benefit in generating twice as much rapid potential power as a four stroke engine. This study is part of a series of research publications on the two-stroke double potential power ecological engine with spark assisted compression ignition, which can maintain lower emissions, better fuel consumption, and fuel type practicality while improving the thermal efficiency of the double power generation. Technical development findings have been reserved for specific purposes; thus, such material will be presented on the basis of conceptual design to qualify for academic publication. As stated in the first reference, the design of the Double Power Ecological Engine has been published, so some detail thermodynamic consideration will not be reworked. The design of a new construction will be characterised, such as managing steps of the combustion cycle, controlling the air-fuel ratio, introducing a new method of eliminating knock limit, and enhancing thermal efficiency.